2016
DOI: 10.1136/bmjdrc-2016-000195
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on the prevalence and components of the metabolic syndrome and the association with cardiovascular disease

Abstract: ObjectiveThe significance of the metabolic syndrome (MS) is debated. We investigated whether MS component (by ATPIII and IDF definitions) clustering and any association between MS and prevalent cardiovascular disease (CVD) varied with age.Research design and methodsIn all, 1429 adults (≥25 years) from randomly selected households in rural Victoria, Australia, were assessed for components of MS and prevalent CVD. The expected prevalence of MS was calculated following a simple probabilistic model using the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 46 publications
7
27
1
2
Order By: Relevance
“…Although MetS prevalence is correlated with age, the association between MetS and cardiovascular risk is noted across age strata. 48,49 In the present study, the effect of IAFA reduction on MetS reversion was independent of age. Third, in order to keep all subjects in a similar lifestyle, we did not design a conventional treatment as controls, and we performed a fixed program regardless of participants' baseline conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Although MetS prevalence is correlated with age, the association between MetS and cardiovascular risk is noted across age strata. 48,49 In the present study, the effect of IAFA reduction on MetS reversion was independent of age. Third, in order to keep all subjects in a similar lifestyle, we did not design a conventional treatment as controls, and we performed a fixed program regardless of participants' baseline conditions.…”
Section: Discussionsupporting
confidence: 52%
“…Some studies showed that the risk of MS increases with age [30], so the variable of age should be adjusted for in risk factor analysis. Central obesity, elevated TG, reduced HDL-C, elevated blood pressure, and elevated fasting glucose are clinical symptoms of MS.…”
Section: Discussionmentioning
confidence: 99%
“…O aumento da prevalência da SM com o avançar da idade é fato frequentemente citado na literatura, mas é importante observar que em vários desses estudos [36][37][38][39][40][41] as faixas etárias analisadas incluíram os idosos como um grupo homogêneo, com idades a partir de 60 ou 65 anos, e geralmente comparados a faixas etárias inferiores. Ao analisar os subgrupos etários como no presente estudo (idosos mais jovens com…”
Section: Resultsunclassified